Quantitative histopathologic assessment of perfusion MRI as a marker of glioblastoma cell infiltration in and beyond the peritumoral edema region. Issue 2 (19th December 2018) - Vallatos, A.; Al‐Mubarak, H.F.I.; Birch, J.L.; Galllagher, L.; Mullin, J.M.; Gilmour, L.; Holmes, W.M.; Chalmers, A.J.
Abstract : Background: Conventional MRI fails to detect regions of glioblastoma cell infiltration beyond the contrast‐enhanced T1 solid tumor region, with infiltrating tumor cells often migrating along host blood vessels. Purpose: To quantitatively and qualitatively analyze the correlation between perfusion MRI signal and tumor cell density in order to assess whether local perfusion perturbation could provide a useful biomarker of glioblastoma cell infiltration. Study Type: Animal model. Subjects: Mice bearing orthotopic glioblastoma xenografts generated from a patient‐derived glioblastoma cell line. Field Strength/Sequences: 7T perfusion images acquired using a high signal‐to‐noise ratio (SNR) multiple boli arterial spin labeling sequence were compared with conventional MRI (T1 /T2 weighted, contrast‐enhanced T1, diffusion‐weighted, and apparent diffusion coefficient). Assessment: Immunohistochemistry sections were stained for human leukocyte antigen (probing human‐derived tumor cells). To achieve quantitative MRI‐tissue comparison, multiple histological slices cut in the MRI plane were stacked to produce tumor cell density maps acting as a "ground truth." Statistical Tests: Sensitivity, specificity, accuracy, and Dice similarity indices were calculated and a two‐tailed, paired t ‐test used for statistical analysis. Results: High comparison test results (Dice 0.62–0.72, Accuracy 0.86–0.88, Sensitivity 0.51–0.7, and Specificity 0.92–0.97) indicate a good segmentation for all imaging modalities and highlight the quality of the MRI tissue assessment protocol. Perfusion imaging exhibits higher sensitivity (0.7) than conventional MRI (0.51–0.61). MRI/histology voxel‐to‐voxel comparison revealed a negative correlation between tumor cell infiltration and perfusion at the tumor margins ( P  = 0.0004). Data Conclusion: These results demonstrate the ability of perfusion imaging to probe regions of low tumor cell infiltration while confirming the sensitivity limitations of conventional imaging modalities. The quantitative relationship between tumor cell density and perfusion identified in and beyond the edematous T2 hyperintensity region surrounding macroscopic tumor could be used to detect marginal tumor cell infiltration with greater accuracy. Level of Evidence : 1 Technical stage : 2 J. Magn. Reson. Imaging 2019;50:529–540.